REBELS FROM MASLOV KUT - N. Sudavtsov (Гуманитарные и юридические исследования, 2021)
The article deals with one of the dramatic events in the history of Russia, the suppression of the uprising of landlord Kalantarov's serfs in the village of Malov Kut, Stavropol province, in January 1853. As a result, more than 160 people were killed and died of wounds.How-ever, this incident is not properly reflected in the literature, apparently based on the fact that in the Stavropol province there were mainly state peasants, not serfs. Peasants of the village of Maslov Kut more than half a century fought against merciless exploitation by landlords, their willfulness, for their freedom, being subjected to cruel punishments. In January 1853, there was the largest performance of peasants of landowners of Kalantarovs. It was suppressed with unprecedented cruelty. By order of the civil Governor, General Volotsky, artillery was usedomen and children. It was essentially the execution of serfs in the village of Maslov Kut. At the provincial Assembly of the nobility G. Kalantarov for the third time was elected the first candidate for the leadership of the nobility. The performance of the peasants caused serious concern in the upper levels of state power. The Emperor Nicholas I in connection with the incident did not approve G. Kalantarov for another term as the leader of the provincial nobility. Outraged by the behavior of the participants of the provincial noble Assembly after it became known about the suppression of the uprising in the estate of Kalantarovs, the Emperor announced the Stavropol nobility the highest reprimand, which was an emergency, which was done by the emperors is extremely rare. But the actions of Governor Volotsky authorities considered correct and no one condemned them. The article also discusses the results of the investigation, the trial of the rebels. At the same time, attention is drawn to the fact that all attempts to resolve the issue of Maslov Kut peasants before the abolition of serfdom were unsuccessful.